MOTIVASI MASYARAKAT PENGUNJUNG MASJID AGUNG ISLAMIC CENTER DI PASIR PENGARAIAN KECAMATAN RAMBAH KABUPATEN ROKAN HULU - ", Febria; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Grand Mosque of Islamic Center of Pasir Pengaraian sub district Rambah Rokan Hulu regency with the aim to identify the profile of visitors, to find the motivation of the society to visit the great mosque of Islam center to know the motivation of the community to visit the Islamic mosque of the Islamic center and to know the activities that are being done in the Great Mosque Islamic Center Pasir Pengaraian. In the data-gathering researchers with observation, interview and documentation techniques. This research uses descriptive quantitative research methods. Sampling in this study is taking samples by accident sampling, this technique is a determination technique based on the spontaneity factor. The sample in this study was 50 people. The result of a descriptive analysis shows that the people who visited the Religious Tourism Mosque Agung Islamic Center Pasir Pengaraian are the average female with an average age of 25, and trained Senior Secondary School. The majority of the visiting community came from the province of Riau, with an unmarried status and generally still students. The motivation of the community to visit the Islamic center of the Great Mosque of Pasir Pengaraian has several reasons, namely: for worship. In terms of these activities, visitors are motivated by the need for charity, comfort in worship, the need for self-cleansing, the need for iktikaf, the fulfilled spiritual needs, the need to perform ablution / washing and the need for sacred sanctuaries. to recite. Community activities when visiting religious journeys through the Great Mosque of the Islamic Center of Sand Pengaraian are as follows: performing rituals / worship, whether mandatory, or the sunnah such as obligatory prayer, charity, remembrance, read the holy book of al quran, listen to da'wah and sunnah prayer.Keywords: Religious Tourism Mosque Great Islamic Center, Visitor Motivation